Constitutional Mandate and International Solidarity: A Legal Study of Indonesia's Aid to Victims of the Gaza Conflict - Siregar, Fritz Edward (Journal of Law, Politic and Humanities, 2025)
This study examines Indonesia's role in responding to the Gaza conflict, a complex international issue with historical, political, legal, and humanitarian dimensions. The Gaza conflict is one of the most complex international issues because it encompasses these same dimensions. For Indonesia, this issue is viewed not only as a matter of foreign policy, but also as the implementation of the constitutional mandate of the nation's founders, as stated in the Preamble to the 1945 Constitution. The first paragraph affirms rejection of all forms of colonialism, and the fourth emphasizes the nation's obligation to contribute to a world order based on independence, peace, and justice. Based on these principles, Indonesia supports Palestine through political diplomacy, humanitarian aid, and international legal advocacy. However, implementing these measures faces significant obstacles, including the Israeli military blockade, internal political fragmentation in Palestine, and the use of veto power in the UN Security Council by the five permanent member states. This study uses a juridical-normative legal approach to systematically evaluate Indonesia's actions based on international legal frameworks and norms. This allows us to understand Indonesia's consistency in providing assistance to Gaza as the implementation of the anti-colonial principle, as well as a moral contribution and constitutional mandate for world peace.